Mobile Gateway for Open Education Resources (Oer): A Case with University Of Swaziland Libraries - Anbu, John Paul; Furvin, Jessie (My University, 2016)
Open educational resources (OER) are free and openly licensed educational materials that can be used for teaching, learning, research, and other purposes. Around the globe there are a number of initiatives which are being experimented in the development of OER. This paper is a case study of the development of a gateway application for the OER material to enhance the teaching and research capability of the University of Swaziland. The development of the desktop OER gateway and the conversion of such a gateway into mobile application gateway are discussed in this paper.
Keywords: Open Educational Resources; OER; mobile application; Open Education; OER Mobile gateway